PECKING ORDER THEORY: PENGARUH PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN PADA KEPUTUSAN PENDANAAN PERUSAHAAN - Dewi, Putu Sri Mae Yanti; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
The aim of this research is to examine the validity of the pecking order theory in explaining companies’ preferences in making financing policy through two main factors, i.e. profitability and growth. This research was conducted on companies listed in the Indonesian Stock Exchange in 2011-2015. Sample chosen by non-probability sampling method with purposive sampling technique. The analysis technique used was logistic regression. Based on the results of the analysis using 90 companies as sample, it can be concluded that: (1) profitability has no effect on financing policy, and (2) contrary to the research hypothesis, growth has negative effect on financing policy. The result indicates that the order of financing preferences in Indonesia is not in accordance with the prediction of the pecking order theory.
Keywords: pecking order theory, profitability, growth, financing policy.